Mőssbauer and Magnetic investigations on OPC blended with Silicafume - D. Govindarajan, N. Anandhan, K. Ragu, S. Barathan, P. Veluchamy (Recent Research in Science and Technology, 2009)
The Mössbauer spectra of optimum amount of (20%) silica fume blended cement paste using CO(Rh) Source have been interpreted for its hydration kinetics using two waters namely DW and EW. The obtained results were correlated with the setting time, compressive strength and magnetic data measurement using Kappa bridge. This is preferred as its offers some resistance to sulphate attack observed from their studies.